Active and recyclable gold metal nanoparticles catalyst supported on nitrogen-doped mesoporous carbon for chemoselective hydrogenation of cinnamaldehyde to cinnamyl alcohol - Nagpure, Atul S.; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (Chemistry-An Asian Journal, 2021)
Several supported gold metal catalysts with different Au nanoparticles sizes were prepared and evaluated for the chemoselective hydrogenation of cinnamaldehyde (CA) to cinnamyl alcohol (CAL). To investigate the structure-activity relationship, stability of catalyst, heterogeneity and recyclability, the structural characteristics of materials and Au catalysts (fresh and spent catalysts) were studied by employing variety of physico-chemical techniques. The interrelationship among Au nanoparticles size (nm) with turnover frequency (h(-1)) of Au catalysts has also been explored. Among the various Au catalysts tested, nitrogen-doped mesoporous carbon (NMC) supported Au catalyst having homogeneously dispersed (78.8%) Au nanoparticles (1.6 nm) synthesized by sol-immobilization method (Au-NMC-SI) demonstrated improved catalytic activity affording 78% CAL selectivity and 94.2% CA conversion without using any promoter. Moreover, Au-NMC-SI catalyst exhibited good recyclability and stability. The catalyst synthesis approach described in this investigation opens up a novel strategy for the design of highly efficient metal nano-catalysts supported on NMC materials.
Keywords: Au Nanoparticles; heterogeneous catalysis; Hydrogenation; Nitrogen-doped mesoporous carbon; Support-Metal interaction